The role of regulatory pressure, performance measurement and risk management in enhancing accountability in Malaysian Public sector - Abu Bakar, Bebe (2016)
The public sector is not an exception when it comes to risks, and the notion of modern accountability demands demonstration of risk management (RM) initiatives. However, the increasing trend of irregularities, non-compliance with regulation and mismanagement of government assets are deteriorating public sector accountability. This scenario has placed existing mechanisms of accountability under challenge as they have eroded public trust and confidence. There are scarce empirical studies on the effect of RM practices on accountability and the drivers of RM practices, in particular regulatory pressure and performance measurement system (PMS) use. To investigate the role of RM practices in enhancing public sector accountability, this study drew upon institutional theory and resource-based view to examine the relationships of regulatory pressure and RM practices, PMS use and RM practices, RM practices and accountability, mediating effect of RM practices in the relationship between regulatory pressure and accountability, and mediating effect of RM practices in the relationship between PMS use and accountability. Survey questionnaires were distributed to 217 Chief Risk Officers, top management and branch managers from the Malaysian Federal Statutory Bodies and their main branch offices. 110 usable responses were analyzed using partial least squares structural equation modeling (PLS-SEM) techniques. The results of the study demonstrated that regulatory pressure and all the dimensions of PMS use except for legitimization have significant positive effects on different dimensions of RM practices. In testing the relationship between RM practices and accountability, it indicated that only risk identification has a significant positive effect on accountability. Furthermore, although risk identification did not mediate the relationship between regulatory pressure and accountability, it mediated the relationship between PMS use for monitoring and accountability as well as the relationship between PMS use for attention-focusing and accountability. These findings have provided knowledge and guidance to public sector managers on the implementation of effective RM to enhance accountability and develop a comprehensive RM policy leading to competitive advantage and sustainable growth.